Professional Ethics in Three Professions during the Holocaust - Polgar, Michael F. (Conatus - Journal of Philosophy, 2019)
Modern scholars and bioethicists continue to learn from the Holocaust. Scholarship and history show that the authoritarian Nazi state limited and steered the development and power of professions and professional ethics during the Holocaust. Eliminationist anti-Semitism drove German professions and many professionals to join in policies and programs of mass deportation and ultimately genocidal mass murder, while also excluding many professionals (including most Jewish professionals) from paid work. For many physicians and other medical professionals, humane and truly ethical practices were limited by constrained professional autonomy and coercive state laws. Education and research in natural sciences were distorted by applications of racist eugenic policies and practices. In law schools and legal professions, professionals were rewarded as judgmental enforcers of state policies, often working with limited independent agency and in the public sphere. Mass harm and mass crimes were therefore perpetrated in accordance with Nazi laws and policies, incorporating professions and professionals into destructive practices, along with other occupational groups.